Islamic Religious Counselors' Da'wah Strategies in Fostering Spiritual Development and Sustaining Inmates' Hope in Correctional Institutions - Ahmad Kharis; Audita Dewi Nugraheni (UIN Siber Syekh Nurjati Cirebon, 2025)
This study explores the da'wah strategies employed by Islamic religious counselors from the Ministry of Religious Affairs in Semarang Regency to enhance the spiritual values of inmates at the Class IIA Correctional Facility in Ambarawa. Using a qualitative-descriptive approach and categorized as field research, the study collects primary data through interviews with religious counselors and inmates, while secondary data are gathered from documentation, photographs, and related records of religious guidance activities. The results indicate that the applied da'wah strategies—sentimental (emotional engagement), rational (Islamic teachings and advice), and sensory (contextual adaptation)—play a significant role in fostering inmates' spiritual awareness. Furthermore, the internalization process of spiritual values follows three stages: takhalli (eliminating negative behavior), tahalli (cultivating noble character), and tajalli (reinforcing self-transformation and faith). The findings show that the systematic and need-based da'wah approach contributes effectively to enhancing inmates’ understanding and practice of Islamic values.